Self-determination in Malaysian education: making decisions and taking action in this era of challenge and opportunity / Dawn Yonally and Stuart Ervay - Yonally, Dawn; Stuart, Ervay (ACRULeT, Faculty of Education & UiTM Press, 2006)
Advances in any culture depend on the ability of its people to develop an infrastructure in which governmental decision-making and action-taking are both systematic and systemic. That has been both the challenge and opportunity faced by the Malaysian people since the nation's independence in 1957, to develop systematic governmental processes that are ongoing and cumulative in their positive effect on the country's institutions. The goal is to make those processes so much a force of habit that they become enmeshed with the existing culture, creating an institutional memory that accepts them as a kind of Malaysian way.